Unfolding authenticity within retail gentrification in Mouraria, Lisbon - Guimarães, Pedro (2021)
Retail gentrification is gaining relevance to study the transformation of several urban districts. In this article we explore the connections between this process and the appropriation and use of the elements of authenticity of a given urban district. Drawing upon the production standpoint, we based our research on the objective, constructivist and existential perspective of the concept of authenticity. We developed fieldwork on Mouraria, a traditional neighbourhood of Lisbon city centre, affected by gentrification as a consequence of a strong growth of tourism in the last decade. Information was collected about the size and evolution of the commercial fabric and business owners were interviewed. Its treatment allows to gather three set of elements that were considered as representative of the authenticity of Mouraria: community values, multiculturality and urban features. The way retail spaces use these elements is diverse and intertwined with the different perspectives of authenticity and, on the part of business owners, arises as a management practice. Although Mouraria can be currently placed within an early stage of retail gentrification, the current pace of retail change and gentrification occurring in the neighbourhood may led to a wider replacement of the commercial fabric with detrimental consequences for local residents.